Assessment of the Supply Chain Management as a Comprehensive Evaluation of the Labour Potential of the Region - Tatyana V. Tselyutina; Tatyana A. Vlasova; Olga A. Timokhina; Yana V. Maslova (International Journal of Supply Chain Management, 2019)
The trajectory of future competitive development of the Russian Federation on the basis of innovation is closely correlated with the development of labor potential, the designation of the vectors of an effective tactical and strategic management which should be based on a comprehensive assessment of its formation, reproduction and applying.The methodological basis of the study were the monographic method, system approach and the method of analysis, statistical and economic analysis techniques, such as clustering and dispersion analysis, as well as principal components method. The research carried out a critical analysis of existing labor potential assessment methodologies at the regional level, which allowed taking into account the identified deficiencies offer the author's approach to express diagnostics, which does not require a special wide survey, allows to get objective results and it is the basis for identifying the most important problems and priority ways of solving them. The essence of the approach is to conduct regional clustering procedure on the level of the state of the labor potential on the basis of the author's indicator system.The result of research was defined typology of the subjects-regions of Central Federal District of Russia, which made it possible to carry out inter-regional comparison of the level of labor potential, taking into account the innovation component, highlight the characteristics of the obtained clusters of regions that are important in the acceptance of administrative solutions.The proposed toolbox can inure as a basis for analysis and information developed at the regional and federal level program activities aimed at formation and development of the labour potential.